1975
DOI: 10.1007/bf01317969
|View full text |Cite
|
Sign up to set email alerts
|

Structural and growth characteristics of two avian reoviruses

Abstract: Two virus strains which had been suspected to be the etiological agents of infectious bursitis (Gumboro disease) and of inclusion body hepatitis of chickens were characterized by their morphology, their peptide composition and the segmented genome of their double-stranded RNA to be typical reoviruses. Although the 2 avian strains did not clearly differ in their serological behaviour, the size of some of their RNA segments were not identical. Both strains replicated in tissue cultures prepared from the chorioal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 13 publications
(5 reference statements)
2
58
0
Order By: Relevance
“…Strain F52/70 (Bygrave & Faragher, 1970), isolated in the UK in 1970, was kindly provided by Dr W. Baxendale (Intervet, UK). Strain Cu-1wt was isolated in Germany in 1976 (Nick et al ., 1976). Strain CJ801 was isolated in China in 1980 (Cao et al ., 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Strain F52/70 (Bygrave & Faragher, 1970), isolated in the UK in 1970, was kindly provided by Dr W. Baxendale (Intervet, UK). Strain Cu-1wt was isolated in Germany in 1976 (Nick et al ., 1976). Strain CJ801 was isolated in China in 1980 (Cao et al ., 1998).…”
Section: Methodsmentioning
confidence: 99%
“…The chicken isolate Cu-1 (Nick et al, 1976) of IBDV represented serotype I. IBDV strain 23/82 isolated from a turkey (Chettle et al, 1985) was kindly supplied by N. E. Reed (Central Veterinary Laboratory, New Haw, Weybridge, U.K.). Both strains were propagated in chicken embryo (CE) cells at 39 °C, and were plaque-purified several times as previously described (Miiller et al, 1986).…”
Section: Viruses and Cellsmentioning
confidence: 99%
“…The basic structure of the infectious bursal disease virus (IBDV), the aetiological agent of a disease of chickens which results in the destruction of the bursa of Fabricius, has been elucidated (Nick et al, 1976; M/iller et al, 1979) and has been shown to exhibit the structural characteristics of the Birnaviridae (Dobos et al, 1979;Brown, 1986). During the past few years isolates of IBDV from turkeys have been reported to be essentially identical to the chicken strains, but the turkey isolates were not pathogenic and could be distinguished by neutralization (McNulty et al, 1979;Jackwood et al, 1982); a second serotype was therefore established (McFerran et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Chickens between 3 and 6 weeks of age are highly susceptible for clinical IBD (Cosgrove, 1962;Hirai et al, 1974d;Ley et al, 1983) when protective levels of neutralizing antibody levels are absent. IBDV is a double-stranded, non-enveloped, icosahedral virus (Delmas et al, 2005) with diameter ranging from 55 to 65 nm (Hirai et al, 1974b;Nick et al, 1976). IBDV belongs to the family Birnaviridae, genus Avibirnavirus.…”
Section: Introductionmentioning
confidence: 99%